2016
DOI: 10.1158/1078-0432.ccr-15-1063
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibition Induces MicroRNA-182, which Targets RAD51 and Impairs HR Repair to Sensitize Cells to Sapacitabine in Acute Myelogenous Leukemia

Abstract: Purpose The double strand breaks elicited by sapacitabine, a clinically active nucleoside analog prodrug are repaired by Rad51 and the homologous recombination repair (HR) pathway which could potentially limit its toxicity. We investigated the mechanism by which HDAC inhibitors targeted Rad51 and HR to sensitize AML cells to sapacitabine. Experimental Design Chromatin immunoprecipitation identified the role of HDACs in silencing microRNA-182 in AML. Immunoblotting, gene expression, overexpression or inhibiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 48 publications
(75 reference statements)
2
40
0
Order By: Relevance
“…In addition, miR-96 is known to down-regulate RAD51 (a DNA repair protein) and REV1 (a DNA polymerase) to promote cellular sensitivity to cisplatin, which binds to and cause crosslinking of DNA to ultimately trigger apoptosis [36]. Similar results were also found for miR-182 in acute myelogenous leukemia [21]. Thus, the over-expression of miR-96/miR-182 appears to dramatically promote drug sensitization in cancer cells [36].…”
Section: Resultsmentioning
confidence: 78%
“…In addition, miR-96 is known to down-regulate RAD51 (a DNA repair protein) and REV1 (a DNA polymerase) to promote cellular sensitivity to cisplatin, which binds to and cause crosslinking of DNA to ultimately trigger apoptosis [36]. Similar results were also found for miR-182 in acute myelogenous leukemia [21]. Thus, the over-expression of miR-96/miR-182 appears to dramatically promote drug sensitization in cancer cells [36].…”
Section: Resultsmentioning
confidence: 78%
“…This study suggested that the binding of miR-197 to RAD51 rs7180135 might alter miR-197-mRNA-binding and might predict sensitivity of tumors to radiotherapy, thus affecting outcomes in bladder cancer 13 . Several other miRNAs have previously been shown to target RAD51 and inhibit its role in homologous recombination repair, including miRNA-182, miR-155, miR-103, and miR-107 in several types of human cancer 37-39 . In addition, miR-182 can impede DNA repair and may increase the susceptibility of breast cancer to radiotherapy and chemotherapy through downregulation of BRCA1 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The recombinase pro- As the HR repair pathway is so important in cell survival and correct replication, it has become a therapeutic target in cancer cells which already contain a DNA repair defects. Molecules which inhibit HR activity, such as Mirin, are in the early phases of development [18]. Mirin inhibits the nuclease activity of Mre11 within the MRN complex, thereby inhibiting the initiation of HR.…”
Section: Homologous Recombinationmentioning
confidence: 99%
“…These small molecule inhibitors, and others similar (such as RAD51 inhibitors), are still in early phase trials. These molecules target HR through various avenues [18]. Targeting cABL and HSP90 are also being investigated in HRR deficient cells [16].…”
Section: Homologous Recombinationmentioning
confidence: 99%